The junipers - McCarthy, Geneva, author; Beachy-Quick, Dan, advisor; Steensen, Sasha, committee member; Moseman, Eleanor, committee member (Colorado State University. Libraries, 2020)
The poems in Geneva McCarthy's thesis, The Junipers, explore intersectionality as a function of sentience-based epistemological and ontological concerns. The pieces explicitly seek to engage the world in terms of connectivity and as a liminal being not exclusively as an existence of isolate cognition. That is to say, that the poems seek to be permeable. In many cases, the poems attempt to be both receptor and resonance: they listen as much as they look. They aspire to feel and not just witness, to think, as it were, through their skin. The work hopes, via these means, to desegregate I and other and increase conversation not solely by speaking, or via themselves as declarative speech acts (as a demonstration of "knowing"), but also by privileging curiosity and actively listening.
Keywords: loss/grief; poetry; synaesthesia; ontology; ecology; sound